Co-evolution of Agent Oriented Conceptual Models and Use Case Diagrams - Bhuiyan, M.; Islam, Z.; Krishna, Aneesh; Ghose, A. (IEEE Computer Society Press, 2006)
Agent-oriented conceptual modeling notations such as i* represents an interesting approach for modeling early phase requirements which includes organizational contexts, stakeholder intentions and rationale. On the other hand, use case diagram is used for capturing functional requirements of the system. The integration of i* model and use case diagram closes the gap of capturing organizational requirements and system requirements. But in both contexts the requirements might change at any time. Any change made in one model must be reflected in the other. This paper proposes a methodology supporting the co-evolution of these two otherwise disparate approaches in a synergistic fashion